Preparation process of negative electrode slurry, negative electrode plate and battery

By preparing negative electrode slurry with low solid content and low viscosity, the problem of difficult reduction of the negative electrode sheet density during high-rate charging and discharging of lithium-ion batteries is solved, and the battery's high-rate charging and discharging performance is improved and the charging time is shortened.

CN119447150AActive Publication Date: 2025-02-14HUIZHOU EVE POWER CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411581258.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-14
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

Existing lithium-ion batteries face the problem of difficult reduction of the negative electrode plate density during high-rate charging and discharging, resulting in long charging time and poor fast charging performance.

Method used

By preparing a negative electrode slurry with low solid content (30-40%) and low viscosity (300-1050mPa·S), the specific ratio and stirring of thickeners, solvents, powder conductive agents and binders are used to obtain the specific ratio and stirring of thickening agents, solvents, powder conductive agents and binders. The process enables long-term dispersion and stability of the negative electrode slurry and prevents re-aggregation and scratches during the coating process.

Benefits of technology

Low-side density coating of the negative electrode sheet is achieved, the high-rate charging and discharging performance of lithium-ion batteries is improved, the charging time is reduced, and the good appearance and stability of the battery is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005123737820000171
    Figure BDA0005123737820000171
  • Figure BDA0005123737820000172
    Figure BDA0005123737820000172
  • Figure BDA0005123737820000181
    Figure BDA0005123737820000181
Patent Text Reader

Abstract

According to the preparation process of the negative electrode slurry, the negative electrode plate and the battery provided by the invention, under the preparation process, the negative electrode slurry can still realize long-term dispersion stability under the conditions of low solid content of 30-40% and low viscosity of 300-1050 mPa.S. And coating with the surface density not higher than 17g / m < 2 > can be realized by utilizing the negative electrode slurry, and meanwhile, obvious scratches cannot be generated in the coating process, so that the negative electrode plate can be ensured to have good appearance and can be applied to actual preparation and production of the lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-ion batteries, and in particular relates to a preparation process of a negative electrode slurry, a negative electrode sheet and a battery. Background Art

[0002] With the application of lithium-ion batteries in the automotive industry, people require shorter charging time and stronger accelerated charging performance, so the high-rate charge and discharge performance of power batteries is increasingly required. For example, in some special-purpose models, the rate requirements far exceed the current level, requiring a charge and discharge rate of >100C or higher. In order for lithium-ion batteries to achieve such a high charge and discharge rate, the electrode thickness needs to be very thin and the surface density very small.

[0003] Currently, the most widely used negative electrode slurry on the market is graphite negative electrode slurry. The solid content of conventional graphite negative electrode slurry is between 48% and 55%, and the viscosity is between 3500 and 8000 mPa.s. If the solid content and viscosity of the graphite-enriched slurry are lower, the dispersion stability of the slurry will deteriorate and the storage time will be short. Even if it is coated at low solid content and low viscosity, it is easy to re-agglomerate. At the same time, it also causes scratches during the coating process, making the negative electrode sheet unable to be used normally. Therefore, low surface density coating of the negative electrode cannot be achieved.

[0004] The lowest single-sided surface density that can be achieved by negative electrode slurry coating in existing industrial plants is about 25g / m 2 When the surface density is further reduced, a large number of scratches will appear on the pole piece, and it will cause scratches on the extrusion coating die lip, resulting in very low manufacturability.

[0005] In view of this, providing a preparation process for low-solid content, low-viscosity negative electrode slurry so that the negative electrode slurry can be dispersed and stably maintained for a long time at low solid content and low viscosity, and preparing negative electrode sheets with lower surface density is of great significance for solving the current problem of fast charging of lithium-ion batteries at higher rates. Summary of the invention

[0006] In order to solve the problems and shortcomings in the prior art, the present invention provides a preparation process of negative electrode slurry, a negative electrode sheet and a battery. Under the preparation process, the negative electrode slurry can achieve long-term dispersion stability at a low solid content of 30-40% and a low viscosity of 300-1050mPa·S. The negative electrode slurry can achieve a surface density of no more than 17g / m 2 The coating can be carried out without obvious scratches during the coating process, so the negative electrode sheet can be guaranteed to have a good appearance and morphology, and can be applied to the preparation and production of actual lithium-ion batteries.

[0007] According to a first aspect of the present invention, a process for preparing a negative electrode slurry is provided, comprising the following steps:

[0008] Step 1. Mix the thickener and solvent B-1 to obtain a main liquid; perform low-speed stirring and high-speed stirring at the same time during the mixing, the low-speed stirring rate is 5 to 30 rpm, the high-speed stirring linear speed is 10 to 20 m / s, and the mixing time is 120 to 400 min; Step 2. Mix the powder conductive agent B and the negative electrode active material, then add the first part of the main liquid B thereto and continue mixing to obtain a first mixed liquid B; perform low-speed stirring during the mixing, the low-speed stirring rate is 10 to 30 rpm, and the mixing time is 120 to 165 min; Step 3. Add the second part of the main liquid B to the first mixed liquid B and mix to obtain a second mixed liquid Liquid B; performing low-speed stirring and high-speed stirring simultaneously during mixing, the low-speed stirring rate is 15-30rpm, the high-speed stirring linear speed is 10-20m / s, and the mixing time is 30-60min; Step 4. Adding binder B to the second mixed liquid B and mixing to obtain a third mixed liquid B; performing low-speed stirring and high-speed stirring simultaneously during mixing, the low-speed stirring rate is 15-30rpm, the high-speed stirring linear speed is 10-20m / s, and the mixing time is 30-90min; Step 5. Adjusting the viscosity of the third mixed liquid B to 300-1050mPa.s and the solid content to 30-40% to obtain a negative electrode slurry.

[0009] In the prior art, in order to improve the energy storage capacity of the battery, the surface density of the electrode is often increased. Increasing the solid content of the slurry is one of the main ways to increase the density of the positive electrode. Generally speaking, there is a certain relationship between the solid content and the viscosity. The higher the solid content, the higher the viscosity. Therefore, the current main research direction tends to increase the solid content and viscosity of the slurry. On the other hand, the viscosity and solid content of the slurry are important factors affecting its stability. Under high solid content and high viscosity, the stability of the slurry is often higher. If the solid content and viscosity of the slurry are to be further reduced, it is often not feasible to directly add solvents, because after the additional addition of solvents, the solid content and viscosity of the slurry are reduced, which will lead to poor stability of the slurry, which is not conducive to the further application of the slurry, such as the production of positive electrode sheets. Reagglomeration is prone to occur during the coating process, and coating scratches are caused.

[0010] At the same time, as a multi-component non-equilibrium system, the biggest problem of slurry is that the internal particles agglomerate due to electrostatic attraction, van der Waals force or hydrogen bonding, or settle under the action of gravity, thus affecting the dispersion uniformity and stability of the slurry. Therefore, in order to make a stable slurry, it is necessary to comprehensively consider the influence of multiple factors such as material properties, formula, mixing process, environment, etc.

[0011] In the preparation process of the negative electrode slurry provided by the present invention, the thickener is first wetted with a solvent and dispersed to obtain the main liquid, and then the main liquid is added to the solid mixture formed by the negative electrode active material and the powder conductive agent B in two times, wherein the first part of the main liquid B is firstly mixed by low-speed stirring, and a preliminary macroscopic dispersion can be performed first, that is, the large powder agglomerates in the solution are broken up, so that the thickener, the negative electrode active material and the powder conductive agent B can be evenly distributed in the solution in the form of fine powder agglomerates. At the same time, because when the first part of the main liquid B is added and mixed, it belongs to liquid-solid mixing. If high-speed stirring is applied at the same time, it is easier to make the thickener, the negative electrode active material and the powder conductive agent B in the solution easily agglomerate and difficult to disperse. Even if it is stirred continuously for a long time, a molecular-level uniform (microscopically dispersed) mixture cannot be obtained, which is not conducive to the long-term dispersion stability of the slurry. Moreover, directly applying high-speed stirring during solid-liquid mixing will also easily cause greater losses to the equipment.

[0012] Then, when the second part of the main liquid B is added and mixed, low-speed stirring and high-speed stirring are carried out simultaneously. At this time, it belongs to liquid-liquid mixing. Before the two solutions are mixed, the materials and solvents in the solution have reached a relatively stable state. At this time, low-speed stirring and high-speed stirring are applied simultaneously, which is conducive to the macroscopic dispersion and microscopic dispersion of the slurry, and finally the slurry reaches a stable dispersion state at a molecular level. That is, the thickener, conductive agent and binder B can be evenly and firmly coated on the surface of the negative electrode active material particles, and at the same time, the interactions such as van der Waals force, electrostatic repulsion, steric repulsion, etc. between the thickener, conductive agent, binder B, negative electrode active material and solvent in the slurry reach a higher stable state, so that the slurry has a higher dispersion stability. Therefore, the slurry in the present invention can maintain long-term stability even at a lower solid content and lower viscosity, and can prevent re-agglomeration and scratches from occurring during the coating process, which is conducive to the preparation of a negative electrode sheet with a low surface density, thereby achieving the purpose of preparing a lithium battery with a high rate of rapid charging.

[0013] It should also be noted that the blade shape in low-speed stirring is generally a twisted blade shape, and the blade shape in high-speed stirring is generally a disc shape with teeth. Of course, the blade shape of low-speed stirring and high-speed stirring can be adjusted according to specific circumstances. In addition, the addition of the binder in two steps at the end will also affect the stability of the final negative electrode slurry. Adding the binder in two steps is conducive to the uniform and stable dispersion of the binder in the slurry system provided by the present invention, further promoting the stability of the slurry.

[0014] Preferably, in step 1, when forming the main liquid, the feed mass ratio of thickener: solvent B-1 is 0.005 to 0.03: 1. At this mass ratio, the solvent can fully wet and disperse the thickener, and the formed main liquid contains enough solvent to promote the subsequent good dispersion of the powder conductive agent B, the negative electrode active material and the binder B.

[0015] Preferably, in step 1, the thickener includes a carboxymethyl cellulose thickener; in step 2, the powder conductive agent B includes a carbon black conductive agent; the negative electrode active material includes a graphite active material; in step 4, the binder B includes an LA aqueous binder B, and the effective ingredients of the LA aqueous binder B include polyacrylic acid compounds and acrylonitrile multipolymers.

[0016] Preferably, the carboxymethyl cellulose thickener includes at least one of carboxymethyl cellulose, sodium carboxymethyl cellulose and lithium carboxymethyl cellulose.

[0017] Preferably, the carbon black conductive agent includes at least one of acetylene black, SP, and Ketjen black.

[0018] Preferably, the graphite-based active material includes at least one of natural graphite and artificial graphite.

[0019] Preferably, the LA aqueous binder B includes at least one of LA132, LA133, and LA136.

[0020] Preferably, the solid content of LA aqueous binder B is 4-15%. Using LA aqueous binder B with a lower solid content has lower viscosity and stirring resistance, which is conducive to its uniform dispersion in the slurry and forms a stable suspension dispersion system with other materials in the slurry.

[0021] Preferably, solvent B-1 comprises water.

[0022] Preferably, in step 2, the D50 of the negative electrode active material is 1 to 20 μm. The negative electrode slurry will have a certain relationship with the D50 of the negative electrode active material, because the negative electrode active material accounts for the largest proportion of the effective components in the negative electrode slurry, and the dispersion stability of the negative electrode active material particles has a very critical influence on the stability of the negative electrode slurry. Controlling the D50 of the negative electrode active material within the above range is conducive to appropriate steric hindrance between the negative electrode active material particles, so that there is a stable interaction force between the particles, and at the same time, the negative electrode active particles can have a stable interaction force with other materials in the slurry, forming a relatively stable suspension dispersion system.

[0023] Preferably, in steps 1 to 2 and 4, the mass ratio of negative electrode active material: main liquid B: binder B: powder conductive agent B is 1: (0.2 to 0.8): (0.1 to 0.6): (0.005 to 0.05). Ensuring that the mass ratio of the above materials is within the above ratio can not only ensure that the materials have a stable interaction force in the formed mixed system to form a long-term stable dispersed suspension system, but also ensure that the negative electrode sheet prepared using the negative electrode slurry system has good conductivity, structural stability, etc., and ensure that the battery prepared with the negative electrode sheet has good cycle performance.

[0024] Preferably, in step 2, the mass proportion of the first part of the main liquid B in the main liquid is 40-50%; the mass proportion of the second part of the main liquid B in the main liquid is 50-60%. The first part of the main liquid B accounts for a relatively small proportion, because at the beginning there are only thickeners and solvents in the main liquid, and the solid content of the main liquid is very low. The main liquid with a relatively small proportion can fully wet and disperse the powder conductive agent B and the negative electrode active material, and at the same time, a well-dispersed suspension system is initially formed only under low-speed stirring. The second part of the main liquid B accounts for a relatively large proportion, and at this time, the solid content and viscosity of the first mixed liquid B are higher, which is conducive to reducing the dispersion resistance and improving the dispersion efficiency and effect.

[0025] Preferably, step 2 is divided into three steps, and the specific operations are as follows: step 2.1. First perform low-speed stirring, the low-speed stirring rate is 15-20rpm, and the mixing time is 30-45min; step 2.2. After step 2.1 is completed, scrape the slurry on the agitator and continue to stir at a low speed, the low-speed stirring rate is 20-30rpm, and the mixing time is 45-60min; step 2.3. After step 2.2 is completed, scrape the slurry on the agitator and continue to stir at a low speed, the low-speed stirring rate is 20-30rpm, and the mixing time is 45-60min. When the first part of the main liquid B is mixed with the powder conductive agent B and the negative electrode active material, since a large number of solid particles of the powder conductive agent B and the positive electrode active material are added at once, low-speed stirring and dispersion are carried out in three steps, which is beneficial to the full wetting and dispersion of the powder conductive agent B and the negative electrode active material in the solution, so that the negative electrode active material, thickener and powder conductive agent B can achieve good macroscopic dispersion, laying the foundation for the subsequent further microscopic dispersion of the slurry, that is, molecular-level dispersion.

[0026] Preferably, in step 5, the viscosity and solid content of the third mixed liquid B are adjusted by adding a second solvent; the second solvent includes water.

[0027] Preferably, in step 5, after adjusting the viscosity and solid content of the third mixed liquid B, it is also necessary to perform iron removal treatment on it.

[0028] According to a second aspect of the present invention, a negative electrode sheet is provided. When preparing the negative electrode sheet, the negative electrode slurry used is prepared by the above-mentioned negative electrode slurry preparation process; the surface density of the negative electrode sheet is 5 to 17 g / m 2 The negative electrode slurry prepared by the present invention can remain stable and stable in dispersion without sedimentation during long-term storage, and will not significantly re-agglomerate during low surface density coating, nor will it cause obvious scratches during the coating process, and has a good appearance, so it can effectively achieve low surface density negative electrode coating, improve the battery charge and discharge rate, and reduce the battery charging time.

[0029] According to a third aspect of the present invention, a battery is provided, comprising the above-mentioned negative electrode sheet. The battery prepared using the above-mentioned negative electrode sheet with lower surface density can achieve higher rate charge and discharge, greatly reducing the charging time of the battery.

[0030] Preferably, the battery further comprises a positive electrode sheet, the surface density of the positive electrode sheet is 10 to 50 g / m 2 .

[0031] Preferably, the surface density of the positive electrode sheet is 10 to 35 g / m 2 .

[0032] Preferably, when preparing the positive electrode sheet, the preparation process of the positive electrode slurry used includes the following steps:

[0033] S1. Mix the binder with the first part of the first solvent to obtain a first mixed liquid; perform low-speed stirring and high-speed stirring simultaneously during mixing, the low-speed stirring rate is 15-30rpm, the high-speed stirring linear speed is 10-20m / s, and the mixing time is 120-400min; S2. Add the liquid conductive agent to the first mixed liquid and mix to obtain a second mixed liquid; perform low-speed stirring and high-speed stirring simultaneously during mixing, the low-speed stirring rate is 15-30rpm, the high-speed stirring linear speed is 10-20m / s, and the mixing time is 60-120min; S3. Mix the powder conductive agent with the second part of the first solvent to obtain a powder conductive agent mixed liquid; add the powder conductive agent mixed liquid to the second mixed liquid and mix to obtain a main liquid; perform low-speed stirring and high-speed stirring simultaneously during mixing, the low-speed stirring rate is 15-30rpm, the high-speed stirring linear speed is 10-20m / s, and the mixing time is 120-180m in; S4. Mix the positive electrode active material with the first part of the main liquid to obtain a third mixed liquid; stir at a low speed during mixing, the low-speed stirring rate is 15-30rpm, and the mixing time is 120-165min; S5. Add the second part of the main liquid to the third mixed liquid and mix to obtain a fourth mixed liquid; stir at a low speed and a high speed at the same time during mixing, the low-speed stirring rate is 15-30rpm, the high-speed stirring line speed is 10-20m / s, and the mixing time is 60-180min; S6. Add the third part of the main liquid to the fourth mixed liquid and mix to obtain a fifth mixed liquid; stir at a low speed and a high speed at the same time during mixing, the low-speed stirring rate is 15-30rpm, the high-speed stirring line speed is 10-20m / s, and the mixing time is 60-180min; S7. Adjust the viscosity of the fifth mixed liquid to 300-1500mPa.s and the solid content to 40-55% to obtain a positive electrode slurry.

[0034] Preferably, in S1 to S3, when forming the main liquid, the feed mass ratio of binder: liquid conductive agent: powder conductive agent: first solvent is 1.0 to 4.0: 10.0 to 30.0: 1.0 to 7.0: 15.0 to 85.0; wherein the total mass of the first solvent is the sum of the mass of the first part of the first solvent and the mass of the second part of the first solvent. Preferably, in S1 and S3, the first solvent includes N-methylpyrrolidone.

[0035] Preferably, in S1, the binder includes polyvinylidene fluoride; in S2, the effective ingredient in the liquid conductive agent includes carbon nanotubes; in S3, the powder conductive agent includes a carbon black conductive agent; and in S4, the positive electrode active material includes a ternary positive electrode active material.

[0036] Preferably, the carbon nanotubes have a diameter of 5 to 40 nm and a length of 20 to 300 μm.

[0037] Preferably, the carbon black conductive agent includes at least one of acetylene black, SP, and Ketjen black.

[0038] Preferably, the ternary positive electrode active material includes at least one of a nickel-cobalt-manganese positive electrode active material and a nickel-cobalt-aluminum positive electrode active material.

[0039] Preferably, the positive electrode active material has a D50 of 1 to 15 μm.

[0040] Preferably, in S2, the solid content of the liquid conductive agent is 4.0-10.0%.

[0041] Preferably, in S3, the solid content of the main liquid is 8-16%.

[0042] Preferably, S4 is divided into three steps, and the specific operations are as follows: S4.1. First perform low-speed stirring, the low-speed stirring rate is 15-20rpm, and the mixing time is 30-45min; S4.2. After step S4.1 is completed, scrape the slurry on the agitator and continue to stir at a low speed, the low-speed stirring rate is 20-30rpm, and the mixing time is 45-60min; S4.3. After step S4.2 is completed, scrape the slurry on the agitator and continue to stir at a low speed, the low-speed stirring rate is 20-30rpm, and the mixing time is 45-60min.

[0043] Preferably, in S4, the mass ratio of the positive electrode active material to the main liquid is 1:0.2-1.

[0044] Preferably, in S4, the mass proportion of the first part of the main liquid in the main liquid is 40-60%; in S5, the mass proportion of the second part of the main liquid in the main liquid is 20-30%; in S6, the mass proportion of the third part of the main liquid in the main liquid is 20-30%.

[0045] Preferably, in S7, the viscosity and solid content of the fifth mixed liquid are adjusted by adding a second solvent; the second solvent comprises N-methylpyrrolidone.

[0046] Preferably, in S7, after adjusting the viscosity and solid content of the fifth mixed liquid, it is also necessary to perform iron removal treatment on it. DETAILED DESCRIPTION

[0047] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only embodiments of a part of the present invention, rather than all embodiments.

[0048] Example 1

[0049] 1. Preparation of negative electrode slurry

[0050] The preparation of the negative electrode slurry in this embodiment follows the following steps:

[0051] Step 1. Mix 0.6 parts of thickener carboxymethyl cellulose with 37.9 parts of water to obtain a main liquid; perform low-speed stirring and high-speed stirring simultaneously during mixing, the low-speed stirring rate is 17 rpm, the high-speed stirring linear speed is 15 m / s, and the mixing time is 260 min;

[0052] Step 2. Mix 1.2 parts of carbon black SP powder conductive agent B and 54.9 parts of artificial graphite negative electrode active material, then add 16.9 parts of the first part of the main liquid B (accounting for 55% of the mass of the main liquid) and continue mixing to obtain the first mixed liquid B, in which the D50 of the negative electrode active material is 5 μm; during mixing, perform the following three steps in sequence:

[0053] Step 2.1. First, perform low-speed stirring, the low-speed stirring rate is 17 rpm, and the mixing time is 38 min;

[0054] Step 2.2. After step 2.1, scrape the slurry off the stirrer and continue stirring at a low speed, the stirring rate is 25 rpm, and the mixing time is 65 min;

[0055] Step 2.3. After step 2.2, scrape the slurry on the stirrer and continue stirring at a low speed, the stirring rate is 25 rpm, and the mixing time is 65 min;

[0056] Step 3. Add 13.8 parts of the second main liquid B (accounting for 45% of the mass of the main liquid) to the first mixed liquid B to obtain a second mixed liquid B; perform low-speed stirring and high-speed stirring simultaneously during mixing, the low-speed stirring rate is 23 rpm, the high-speed stirring linear speed is 15 m / s, and the mixing time is 45 min;

[0057] Step 4. Add 18.3 parts of binder BLA132 (solid content 6%) to the second mixed solution B to obtain a third mixed solution B; perform low-speed stirring and high-speed stirring simultaneously during mixing, the low-speed stirring rate is 22 rpm, the high-speed stirring linear speed is 15 m / s, and the mixing time is 60 min;

[0058] Step 5. The viscosity of the third mixed solution B is adjusted to 522 mPa.s and the solid content is adjusted to 32.0%. After filtering and removing iron, the negative electrode slurry is obtained.

[0059] 2. Preparation of batteries

[0060] (1) Preparation of negative electrode

[0061] The negative electrode slurry prepared above was coated on the negative electrode current collector (copper foil), and the coating parameters were adjusted so that the surface density of the final negative electrode sheet was 15.2 g / m 2 At this surface density, the negative electrode sheet has a good appearance and no scratches.

[0062] (2) Preparation of positive electrode

[0063] The surface density of this embodiment is 28.5 g / m 2 The positive electrode sheet is of good appearance and has no scratches at this surface density.

[0064] In the positive electrode sheet of this embodiment, the preparation process of the positive electrode slurry used includes the following steps:

[0065] S1. 2.2 parts of PVDF binder and 18.0 parts of N-methylpyrrolidone were mixed to obtain a first mixed solution; low-speed stirring and high-speed stirring were performed simultaneously during the mixing, the low-speed stirring rate was 20 rpm, the high-speed stirring linear speed was 15 m / s, and the mixing time was 260 min;

[0066] S2. 13.3 parts of the liquid conductive carbon nanotube dispersion (solid content 6%) were added to the first mixed solution to obtain a second mixed solution; low-speed stirring and high-speed stirring were performed simultaneously during the mixing, the low-speed stirring rate was 28 rpm, the high-speed stirring linear speed was 15 m / s, and the mixing time was 90 min;

[0067] S3. Mix 3.8 parts of powder conductive agent carbon black SP with 4.0 parts of N-methylpyrrolidone to obtain a powder conductive agent mixed liquid; add the powder conductive agent mixed liquid to the second mixed liquid and mix to obtain a main liquid; perform low-speed stirring and high-speed stirring at the same time during mixing, the low-speed stirring rate is 28rpm, the high-speed stirring linear speed is 15m / s, and the mixing time is 90min; the solid content of the main liquid obtained in this step is 16%;

[0068] S4. After mixing 120.4 parts of the positive electrode active material NCM811 with 16.5 parts of the first part of the main solution (accounting for 40% of the mass of the main solution), wherein the D50 of the positive electrode active material is 7 μm, the following three steps are performed in sequence:

[0069] S4.1 firstly performs low-speed stirring, the low-speed stirring rate is 17 rpm, and the mixing time is 48 min;

[0070] S4.2. After step S4.1 is completed, the slurry on the stirrer is scraped off and continued to stir at a low speed, the low-speed stirring rate is 25 rpm, and the mixing time is 50 min;

[0071] S4.3. After step S4.2 is completed, the slurry on the stirrer is scraped off and then the low-speed stirring is continued. The low-speed stirring rate is 25 rpm and the mixing time is 50 min.

[0072] S5. 12.4 parts of the second main liquid (accounting for 30% of the mass of the main liquid) were added to the third mixed liquid to obtain a fourth mixed liquid; low-speed stirring and high-speed stirring were performed simultaneously during mixing, the low-speed stirring rate was 28 rpm, the high-speed stirring linear speed was 15 m / s, and the mixing time was 120 min;

[0073] S6. 12.4 parts of the third main liquid (accounting for 30% of the mass of the main liquid) were added to the fourth mixed liquid to obtain a fifth mixed liquid; low-speed stirring and high-speed stirring were performed simultaneously during the mixing, the low-speed stirring rate was 28 rpm, the high-speed stirring linear speed was 15 m / s, and the mixing time was 120 min;

[0074] S7. The viscosity of the fifth mixed solution is adjusted to 480 mPa.s and the solid content is adjusted to 54.3%. After filtering and removing iron, a positive electrode slurry is obtained.

[0075] (3) Battery assembly

[0076] The positive electrode sheet, separator and negative electrode sheet are assembled in sequence, the obtained battery cell is placed in a shell, and the electrolyte is injected, formed, and constant volume is obtained to obtain a battery. The formula of the electrolyte is as follows: 1 mol / L LiPF6 ethylene carbonate EC+diethyl carbonate DEC+dimethyl carbonate DMC (volume ratio 1:1:1).

[0077] Example 2

[0078] 1. Preparation of negative electrode slurry

[0079] The preparation of the negative electrode slurry in this embodiment is different from that in Example 1 in that, in step 1, when preparing the main liquid, 0.4 parts of carboxymethyl cellulose and 22.7 parts of water are used as thickeners, 1.2 parts of powder conductive agent B carbon black SP and 55.2 parts of artificial graphite of negative electrode active material are used in step 2, and 18.3 parts of binder B LA132 (solid content 6%) are used in step 4, that is, the mass ratio of negative electrode active material (artificial graphite): main liquid B: binder B (LA132): powder conductive agent B (carbon black SP) is 1:0.42:0.33:0.02; and after adjusting the viscosity and solid content of the third mixed liquid B in step 5, the viscosity of the negative electrode slurry is 413mPa.s and the solid content is 31.8%. The rest is the same as in Example 1.

[0080] 2. Preparation of batteries

[0081] (1) Preparation of negative electrode

[0082] The negative electrode slurry prepared above was coated on the negative electrode current collector (copper foil), and the coating parameters were adjusted so that the surface density of the final negative electrode sheet was 15.6 g / m 2 At this surface density, the negative electrode sheet has a good appearance and no scratches.

[0083] (2) Preparation of positive electrode

[0084] The surface density of this embodiment is 28.6 g / m 2 The positive electrode sheet is of good appearance and has no scratches at this surface density.

[0085] In the positive electrode sheet of this embodiment, the preparation process of the positive electrode slurry used is the same as that of Example 1.

[0086] (3) Battery assembly

[0087] The battery assembly in this embodiment is consistent with that in Embodiment 1.

[0088] Example 3

[0089] 1. Preparation of negative electrode slurry

[0090] The preparation of the negative electrode slurry in this embodiment is different from that in Example 1 in that, in step 1, when preparing the main liquid, 0.2 parts of carboxymethyl cellulose and 11.4 parts of water are used as thickeners, 1.2 parts of powder conductive agent B carbon black SP and 55.3 parts of artificial graphite of the negative electrode active material are used in step 2, and 18.3 parts of binder BLA132 (solid content 6%) are used in step S4, that is, the mass ratio of negative electrode active material (artificial graphite): main liquid B: binder B (LA132): powder conductive agent B (carbon black SP) is 1:0.28:0.33:0.02; and after adjusting the viscosity and solid content of the third mixed liquid B in step 5, the viscosity of the negative electrode slurry is 335mPa.s and the solid content is 31.9%. The rest is the same as in Example 1.

[0091] 2. Preparation of batteries

[0092] (1) Preparation of negative electrode

[0093] The negative electrode slurry prepared above was coated on the negative electrode current collector (copper foil), and the coating parameters were adjusted so that the surface density of the final negative electrode sheet was 14.8 g / m 2 At this surface density, the negative electrode sheet has a good appearance and no scratches.

[0094] (2) Preparation of positive electrode

[0095] The surface density of this embodiment is 28.5 g / m 2 The positive electrode sheet is of good appearance and has no scratches at this surface density.

[0096] In the positive electrode sheet of this embodiment, the preparation process of the positive electrode slurry used is consistent with that of Example 1.

[0097] (3) Battery assembly

[0098] The battery assembly in this embodiment is consistent with that in Embodiment 1.

[0099] Example 4

[0100] 1. Preparation of negative electrode slurry

[0101] The preparation of the negative electrode slurry in this embodiment is different from that in Example 1 in that, in step 1, when preparing the main liquid, 0.5 parts of carboxymethyl cellulose as a thickener and 30.3 parts of water are used, 1.2 parts of carbon black SP as a powder conductive agent B and 55.7 parts of artificial graphite as a negative electrode active material are used in step 2, and 6.7 parts of binder BLA132 (solid content 6%) are used in step 4, that is, the mass ratio of negative electrode active material (artificial graphite): main liquid B: binder B (LA132): powder conductive agent B (carbon black SP) is 1:0.56:0.12:0.02; and after adjusting the viscosity and solid content of the third mixed liquid B in step 5, the viscosity of the negative electrode slurry is 157mPa.s and the solid content is 31.6%. The rest is the same as in Example 1.

[0102] 2. Preparation of batteries

[0103] (1) Preparation of negative electrode

[0104] The negative electrode slurry prepared above was coated on the negative electrode current collector (copper foil), and the coating parameters were adjusted so that the surface density of the final negative electrode sheet was 15.2 g / m 2 At this surface density, the negative electrode sheet has a good appearance and no scratches.

[0105] (2) Preparation of positive electrode

[0106] The surface density of this embodiment is 28.5 g / m 2 The positive electrode sheet is of good appearance and has no scratches at this surface density.

[0107] In the positive electrode sheet of this embodiment, the preparation process of the positive electrode slurry used is consistent with that of Example 1.

[0108] (3) Battery assembly

[0109] The battery assembly in this embodiment is consistent with that in Embodiment 1.

[0110] Example 5

[0111] 1. Preparation of negative electrode slurry

[0112] The preparation of the negative electrode slurry in this embodiment is different from that in Example 1 in that, in step 1, when preparing the main liquid, 0.5 parts of thickener carboxymethyl cellulose and 30.3 parts of water are used, 1.2 parts of powder conductive agent B carbon black SP and 54.0 parts of negative electrode active material artificial graphite are used in step 2, and 35.36 parts of binder BLA132 (solid content 6%) are used in step 4, that is, the mass ratio of negative electrode active material (artificial graphite): main liquid B: binder B (LA132): powder conductive agent B (carbon black SP) is 1:0.57:0.65:0.02; and after adjusting the viscosity and solid content of the third mixed liquid B in step 5, the viscosity of the negative electrode slurry is 950mPa.s and the solid content is 29.5%. The rest is the same as in Example 1.

[0113] 2. Preparation of batteries

[0114] (1) Preparation of negative electrode

[0115] The negative electrode slurry prepared above was coated on the negative electrode current collector (copper foil), and the coating parameters were adjusted so that the surface density of the final negative electrode sheet was 15.0 g / m 2 At this surface density, the negative electrode sheet has a good appearance and no scratches.

[0116] (2) Preparation of positive electrode

[0117] The surface density of this embodiment is 28.5 g / m 2 The positive electrode sheet is of good appearance and has no scratches at this surface density.

[0118] In the positive electrode sheet of this embodiment, the preparation process of the positive electrode slurry used is consistent with that of Example 1.

[0119] (3) Battery assembly

[0120] The battery assembly in this embodiment is consistent with that in Embodiment 1.

[0121] Example 6

[0122] 1. Preparation of negative electrode slurry

[0123] The preparation of the negative electrode slurry in this embodiment is different from that in Example 1 in that, in step 1, when preparing the main liquid, 0.8 parts of carboxymethyl cellulose and 44.7 parts of water are used as thickeners, 1.3 parts of powder conductive agent B carbon black SP and 53.8 parts of artificial graphite of the negative electrode active material are used in step 2, and 31.5 parts of binder BLA132 (solid content 6%) are used in step 4, that is, the mass ratio of negative electrode active material (artificial graphite): main liquid B: binder B (LA132): powder conductive agent B (carbon black SP) is 1:0.85:0.59:0.02; and after adjusting the viscosity and solid content of the third mixed liquid B in step 5, the viscosity of the negative electrode slurry is 873mPa.s and the solid content is 28.8%. The rest is the same as in Example 1.

[0124] 2. Preparation of batteries

[0125] (1) Preparation of negative electrode

[0126] The negative electrode slurry prepared above was coated on the negative electrode current collector (copper foil), and the coating parameters were adjusted so that the surface density of the final negative electrode sheet was 15.0 g / m 2 At this surface density, the negative electrode sheet has a good appearance and no scratches.

[0127] (2) Preparation of positive electrode

[0128] The surface density of this embodiment is 28.5 g / m 2 The positive electrode sheet is of good appearance and has no scratches at this surface density.

[0129] In the positive electrode sheet of this embodiment, the preparation process of the positive electrode slurry used is consistent with that of Example 1.

[0130] (3) Battery assembly

[0131] The battery assembly in this embodiment is consistent with that in Embodiment 1.

[0132] Example 7

[0133] The preparation of the negative electrode slurry in this embodiment is different from that in embodiment 1 in that the mixing is not performed in three steps in step 2, but directly in one step, specifically: the powder conductive agent B and the negative electrode active material are mixed, and then the first part of the main liquid B is added thereto and mixed continuously to obtain the first mixed liquid B, and low-speed stirring is performed during mixing, the low-speed stirring rate is 25 rpm, and the mixing time is 168 min; and finally, after adjusting the viscosity and solid content of the third mixed liquid B in step 5, the viscosity of the negative electrode slurry is 872 mPa.s and the solid content is 27.5%. The rest is the same as in embodiment 1.

[0134] 2. Preparation of batteries

[0135] (1) Preparation of negative electrode

[0136] The negative electrode slurry prepared above was coated on the negative electrode current collector (copper foil), and the coating parameters were adjusted so that the surface density of the final negative electrode sheet was 15.2 g / m 2 At this surface density, the negative electrode sheet has a good appearance and no scratches.

[0137] (2) Preparation of positive electrode

[0138] The surface density of this embodiment is 28.5 g / m 2 The positive electrode sheet is of good appearance and has no scratches at this surface density.

[0139] In the positive electrode sheet of this embodiment, the preparation process of the positive electrode slurry used is consistent with that of Example 1.

[0140] (3) Battery assembly

[0141] The battery assembly in this embodiment is consistent with that in Embodiment 1.

[0142] Comparative Example 1

[0143] 1. Preparation of negative electrode slurry

[0144] The preparation of the negative electrode slurry in this comparative example follows the following steps:

[0145] Step 1. Mix 0.6 parts of thickener carboxymethyl cellulose with 37.9 parts of water to obtain a main liquid; perform low-speed stirring and high-speed stirring simultaneously during mixing, the low-speed stirring rate is 17 rpm, the high-speed stirring linear speed is 15 m / s, and the mixing time is 260 min;

[0146] Step 2. Mix 1.2 parts of carbon black SP powder conductive agent B and 54.9 parts of artificial graphite negative electrode active material, then add 30.7 parts of main liquid (all main liquid) and continue mixing to obtain a first mixed liquid B, in which the D50 of the negative electrode active material is 5 μm; stir at a low speed during mixing, the low speed stirring rate is 25 rpm, and the time is 168 min; then stir at a low speed and at a high speed at the same time, the low speed stirring rate is 23 rpm, the high speed stirring linear speed is 15 m / s, and the mixing time is 45 min;

[0147] Step 3. Add 18.3 parts of binder B to the first mixed solution B to obtain a second mixed solution B; perform low-speed stirring and high-speed stirring simultaneously during mixing, the low-speed stirring rate is 25 rpm, the high-speed stirring linear speed is 15 m / s, and the mixing time is 120 min;

[0148] Step 4. The viscosity of the second mixed solution B is adjusted to 823 mPa.s and the solid content is adjusted to 30.5%. After filtering and removing iron, the negative electrode slurry is obtained.

[0149] 2. Preparation of batteries

[0150] (1) Preparation of negative electrode

[0151] The negative electrode slurry prepared above was coated on the negative electrode current collector (copper foil), and the coating parameters were adjusted so that the surface density of the final negative electrode sheet was 15.2 g / m 2 At this surface density, the negative electrode sheet has a good appearance and no scratches.

[0152] (2) Preparation of positive electrode

[0153] The surface density of this comparative example is 28.5 g / m 2 The positive electrode sheet is of good appearance and has no scratches at this surface density.

[0154] In the positive electrode sheet of this comparative example, the preparation process of the positive electrode slurry used is consistent with that of Example 1.

[0155] (3) Battery assembly

[0156] The battery assembly in this comparative example is consistent with that in Example 1.

[0157] Comparative Example 2

[0158] 1. Preparation of negative electrode slurry

[0159] The preparation of the negative electrode slurry in this comparative example follows the following steps:

[0160] Step 1. Mix 0.6 parts of thickener carboxymethyl cellulose with 37.9 parts of water to obtain a main liquid; perform low-speed stirring and high-speed stirring simultaneously during mixing, the low-speed stirring rate is 17 rpm, the high-speed stirring linear speed is 15 m / s, and the mixing time is 260 min;

[0161] Step 2. Mix 1.2 parts of powder conductive agent B carbon black SP and 54.9 parts of negative electrode active material artificial graphite, then add 30.7 parts of main liquid (all main liquid) and 18.3 parts of binder B (all binder B) to continue mixing to obtain a first mixed liquid B, in which the D50 of the negative electrode active material is 5 μm; stir at a low speed first, the low speed stirring rate is 25 rpm, and the time is 168 min; then stir at a low speed and high speed at the same time, the low speed stirring rate is 23 rpm, the high speed stirring linear speed is 15 m / s, and the mixing time is 105 min;

[0162] Step 3. The viscosity of the first mixed solution B is adjusted to 750 mPa.s and the solid content is adjusted to 29.7%. After filtering and removing iron, a negative electrode slurry is obtained.

[0163] 2. Preparation of batteries

[0164] (1) Preparation of negative electrode

[0165] The negative electrode slurry prepared above was coated on the negative electrode current collector (copper foil), and the coating parameters were adjusted so that the surface density of the final negative electrode sheet was 15.4 g / m 2 At this surface density, the negative electrode sheet has a good appearance and no scratches.

[0166] (2) Preparation of positive electrode

[0167] The surface density of this comparative example is 28.5 g / m 2 The positive electrode sheet is of good appearance and has no scratches at this surface density.

[0168] In the positive electrode sheet of this comparative example, the preparation process of the positive electrode slurry used is consistent with that of Example 1.

[0169] (3) Battery assembly

[0170] The battery assembly in this comparative example is consistent with that in Example 1.

[0171] Comparative Example 3

[0172] 1. Preparation of negative electrode slurry

[0173] This comparative example directly uses commercially available conventional graphite negative electrode slurry, wherein the viscosity is 3000 mPa.s and the solid content is 53.0%.

[0174] 2. Preparation of batteries

[0175] (1) Preparation of negative electrode

[0176] The negative electrode slurry prepared above was coated on the negative electrode current collector (copper foil), and the coating parameters were adjusted so that the surface density of the final negative electrode sheet was 25 g / m 2 At this surface density, the negative electrode sheet has a good appearance and no scratches.

[0177] (2) Preparation of positive electrode

[0178] This comparative example uses commercially available 2 The positive electrode sheet has good appearance and no scratches at this surface density.

[0179] (3) Battery assembly

[0180] The battery assembly in this comparative example is consistent with that in Example 1.

[0181] Test Case

[0182] 1. Experimental Construction Method

[0183] (1) Negative electrode slurry performance test

[0184] The viscosity and solid content of the negative electrode slurries prepared in all the above embodiments and comparative examples are statistically analyzed, and the solid content fluctuation value of the negative electrode slurries is calculated after being stored for 24 hours. The calculation formula is as follows: solid content fluctuation value = solid content of the lower layer after the negative electrode slurry is stored for 24 hours - solid content of the negative electrode slurry before storage. Regarding the solid content of the lower layer after the negative electrode slurry is stored for 24 hours, this means, for example, that the negative electrode slurry is placed in a beaker, and after storage for 24 hours, the negative electrode slurry at the bottom of the beaker is taken for testing; and regarding the solid content before the negative electrode slurry is stored, this means, for example, that the negative electrode slurry is placed in a beaker, and the negative electrode slurry has just been stirred and mixed evenly, and the negative electrode slurry at any part of the beaker can be taken for solid content testing.

[0185] (2) Negative electrode performance test

[0186] The surface density of the negative electrode sheets prepared in all the above embodiments and comparative examples was statistically analyzed, and the appearance of the negative electrode sheets obtained after coating was observed.

[0187] (3) Battery performance test

[0188] The batteries prepared in all the above embodiments and comparative examples were tested for cycle capacity retention at discharge rates of 1C, 10C, 30C, 50C, 70C, and 100C, respectively. The specific charge and discharge test operation is as follows: Under a 25°C environment, the divided battery is charged to 4.2V with a 1C constant current and constant voltage, the cut-off current is 0.02C, and left for 5 minutes, and then discharged to 3.0V with 1C, 10C, 30C, 50C, 70C, and 100C, respectively. The capacity retention rate is calculated as follows: Taking the 1C discharge capacity as the benchmark, the discharge capacity at each rate is divided by the benchmark capacity.

[0189] Meanwhile, the DCR (direct current resistance) test was performed on the batteries prepared in all the above embodiments and comparative examples. The specific test method is as follows: after 6000 cycles, discharge at 1C for 10S at 50% SOC, and calculate △V / △I.

[0190] 2. Experimental results

[0191] The relevant performance test results of the negative electrode slurries, negative electrode sheets and batteries prepared in all the above embodiments and comparative examples are shown in Tables 1 and 2.

[0192] Table 1 Performance test results of negative electrode slurry and negative electrode sheet in the embodiments and comparative examples

[0193]

[0194] Table 2 Performance test results of batteries in the embodiments and comparative examples

[0195]

[0196]

[0197] As can be seen from Tables 1 and 2, the negative electrode slurry prepared by the pulping process of the present application has the characteristics of low viscosity and low solid content, the slurry is stable, has good coating performance, and meets the requirements of low surface density coating and maintaining good electrode appearance. The battery prepared using the low surface density negative electrode sheet has good fast charging performance, still has a high cycle capacity retention rate after charging and discharging at a high rate, and has a low resistance, thus greatly optimizing the fast charging performance of the battery. Please refer to the performance data in Examples 1 to 7 for details.

[0198] In comparative example 1, the main liquid is added in one step in step 2, that is, the main liquid is directly mixed; in comparative example 2, the main liquid and the binder are all added at the same time; in comparative example 3, a conventional commercially available negative electrode slurry is used, which has high solid content, high viscosity, and high surface density of the pole piece. The above reasons all lead to a decrease in the storage stability of the negative electrode slurry (the solid content fluctuates greatly after 24 hours), and the slurry material is not dispersed or re-agglomerated after dispersion, which leads to light scratches on the negative electrode sheet and poor coating appearance, resulting in a significant decrease in the cycle capacity retention rate of the battery at a larger rate (such as 70C and 100C), and the DCR of the battery is also significantly increased, and the fast charging performance is poor. It can also be seen that the high-viscosity and high-solid content slurry in comparative example 3 cannot achieve the coating of the low surface density pole piece, and it is impossible to prepare a low surface density negative electrode sheet.

[0199] Further observation of Examples 1 to 4 shows that when the ratio of each material in the process of preparing the negative electrode slurry is changed, although the viscosity, solid content, storage stability, etc. of the positive electrode slurry are not much different, it will have a certain impact on the capacity retention rate of the battery prepared using it at a higher rate. The battery prepared in Example 1 has better comprehensive performance.

[0200] Comparing Example 1 with Examples 5-6, the mass ratio of the negative electrode active material (artificial graphite), main liquid B, binder B (LA132), and powder conductive agent B (carbon black SP) in the process of preparing the negative electrode slurry in Examples 5 and 6 is not in the range of 1: (0.2-0.8): (0.105-0.6): (0.005-0.0405), which will lead to a decrease in the mutual force when the materials are mixed, resulting in poor 24h storage stability of the slurry, and at the same time causing the capacity retention rate of the battery at a higher rate to decrease.

[0201] Comparing Example 1 and Example 7, in Example 7, step 2 is not divided into three steps of low-speed stirring, that is, low-speed stirring is directly performed in one step, which will cause the slurry to agglomerate slightly and have poor 24h storage stability. As a result, slight scratches will appear when the negative electrode sheet is rolled, and the capacity retention rate of the battery at a higher rate will also decrease.

[0202] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.

Claims

1. A process for preparing a negative electrode slurry, characterized in that: The steps include: Step 1. Mix the thickener and solvent B-1 to obtain a main liquid; perform low-speed stirring and high-speed stirring simultaneously during the mixing, the low-speed stirring rate is 5 to 30 rpm, the high-speed stirring linear speed is 10 to 20 m / s, and the mixing time is 120 to 400 min; Step 2. Mix the powder conductive agent B and the negative electrode active material, then add the first part of the main solution B and continue mixing to obtain the first mixed solution B; stir at a low speed during mixing, the low speed stirring rate is 10 to 30 rpm, and the mixing time is 120 to 165 min; Step 3. Add the second part of the main liquid B into the first mixed liquid B to obtain a second mixed liquid B; perform low-speed stirring and high-speed stirring simultaneously during mixing, the low-speed stirring rate is 15-30 rpm, the high-speed stirring linear speed is 10-20 m / s, and the mixing time is 30-60 min; Step 4. Add binder B to the second mixed solution B to obtain a third mixed solution B; perform low-speed stirring and high-speed stirring simultaneously during mixing, the low-speed stirring rate is 15 to 30 rpm, the high-speed stirring linear speed is 10 to 20 m / s, and the mixing time is 30 to 90 min; Step 5. Adjust the viscosity of the third mixed solution B to 300-1050 mPa.s and the solid content to 30-40% to obtain the negative electrode slurry.

2. The process for preparing the negative electrode slurry according to claim 1, characterized in that: In the step 1, when the main liquid is formed, the feed mass ratio of the thickener to the solvent B-1 is 0.005 to 0.03:

1.

3. The process for preparing the negative electrode slurry according to claim 1, characterized in that: In the step 1, the thickener includes a carboxymethyl cellulose thickener; In the step 2, the powder conductive agent B includes a carbon black conductive agent; the negative electrode active material includes a graphite active material; In the step 4, the binder B includes LA water-based binder B, and the effective components of the LA water-based binder B include polyacrylic acid compounds and acrylonitrile multipolymers.

4. The process for preparing the negative electrode slurry according to claim 3, characterized in that: The solid content of the LA aqueous binder B is 4-15%.

5. The process for preparing the negative electrode slurry according to claim 1, characterized in that: In the step 2, the D50 of the negative electrode active material is 1 to 20 μm.

6. The process for preparing the negative electrode slurry according to claim 1, characterized in that: In steps 1 to 2 and 4, the mass ratio of the negative electrode active material: main liquid B: binder B: powder conductive agent B is 1: (0.2 to 0.8): (0.05 to 0.6): (0.005 to 0.05).

7. The process for preparing the negative electrode slurry according to claim 1, characterized in that: In step 2, the mass proportion of the first part of the main liquid B in the main liquid is 40-50%; The mass proportion of the second part of the main liquid B in the main liquid is 50-60%.

8. The process for preparing the negative electrode slurry according to claim 1, characterized in that: The step 2 is divided into three steps, and the specific operations are as follows: Step 2.

1. First, stir at a low speed of 15 to 20 rpm for 30 to 45 min; Step 2.

2. After step 2.1, scrape the slurry on the stirrer and continue stirring at a low speed, the stirring rate is 20 to 30 rpm, and the mixing time is 45 to 60 min; Step 2.

3. After step 2.2, scrape the slurry on the stirrer and continue stirring at a low speed. The low-speed stirring rate is 20 to 30 rpm and the mixing time is 45 to 60 minutes.

9. A negative electrode sheet, characterized in that: When preparing the negative electrode sheet, the negative electrode slurry used is prepared by the negative electrode slurry preparation process as claimed in claims 1 to 8; The surface density of the negative electrode sheet is 5 to 17 g / m 2 .

10. A battery, characterized in that: Comprising the negative electrode sheet as claimed in claim 9.

Citation Information

Patent Citations

  • Negative electrode slurry, negative electrode plate and preparation method of negative electrode plate

    CN111509231A

  • Preparation method of negative electrode slurry, negative electrode plate and battery

    CN117174830A

  • Preparation process of negative electrode slurry, negative electrode plate and battery

    CN118335911A

  • Slurry for lithium ion battery negative electrode, method for manufacturing the same, negative electrode for lithium ion battery, and lithium ion battery

    JP2018006334A